Specification Decision Support System at The Faculty Of Engineering Muhammadiyah University Bengkulu Using Method Simple Additve Weighting (SAW) - Ujang Juhardi; Andilala Andilala; Pahrizal Pahrizal; Muntahanah Muntahanah; Sella Shopiana (Jurnal Komputer, Informasi dan Teknologi, 2022)
The title of this research is a specialization decision support system at the Faculty of Engineering, University of Muhammadiyah Bengkulu using the Simple Additive Weighting (SAW) method. The main problem is how to make an information system in decision making at the Faculty of Engineering, University of Muhammadiyah Bengkulu. This decision support system uses the SAW method. The SAW method was chosen because it determines the weight for each art or criterion, then proceeds with a ranking process that will select the best alternative from a number of existing alternatives. Based on the SAW discussion carried out with data on the value of a student named Andi Prasetio NPM 19552051, the ranking results for Robotics specialization with a value of 56.1 Multimedia specialization with a value of 45.2 Network Specialization with a value of 45.2 and the largest value is Programming specialization with a value of 56 ,6. thus the chosen alternative is Programming specialization. It is hoped that the existence of this specialization decision support system can help provide recommendations for students of the Faculty of Engineering, University of Muhammadiyah Bengkulu in determining the specialization to be taken.